Relationship between aerobic fitness and metabolic recovery from intermittent exercise in endurance athletes - Bell, G. J.; Snydmiller, G. D.; Davies, D. S.; Quinney, H. A. (Canadian Journal of Applied Physiology, 1997)
This investigation examined the relationship between several different aerobic fitness test results and measurements of metabolic recovery from intermittent, high-intensity exercise in 16 male cyclists. No significant correlations were found between maximal oxygen consumption, ventilation threshold, various submaximal endurance measures and the rate of metabolic recovery, net excess postexercise oxygen consumption, or blood lactate removal after intermittent high-intensity exercise except for submaximal heart rate (r = .66, p < .05). These data indicate that aerobic fitness assessments do not indicate the ability to recover after intermittent, high-intensity exercise in endurance-trained cyclists.